AKSES DAN DAMPAK KREDIT MIKRO TERHADAP PRODUKSI PADI ORGANIK DI KABUPATEN BOGOR - Dewi Rohma Wati; Nunung Nuryartono; Lukytawati Anggraeni (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2014)
The ultimate problem of organic paddy farm is limited access formal credit due to collateral requirement. Farmers only have access to semi-formal institution like cooperatives and group of farmers (Gapoktan.red) because of simplicity of administration procedure and payment system. The objectives of this study are to analized accessibility of micro-credit to organic paddy farmers in Bogor and its impact to production of organic paddy. With Heckman Sample Selection Model, we found that access of credit influenced negatively by age of farmers, number of household member, membership of farm group, and the acreage of land use. Microcredit give significant impact to production of organic paddy and it is simultaneous with fertilizer and labor. Microcredit that they have taken used to pay labor and also bought the fertilizer. Keywords : access of microcredit, impact of microcredit, production of organic paddy